PERCOBAAN FRAKSIONASI DISTILASI MINYAK KENANGA DARI CIREBON - Bambang Wiyono; Mohammad Rosid (Jurnal Penelitian Hasil Hutan, 1990)
The  purpose  of  the  research  is to study the properties of  fractional distilled   cananga oil compared  with  Indonesia Industrial Standard requirement for cananga  oil  and  with  ylangylang oil properties of  the  third  fraction (the  lowest quality  of  ylangylang  oil).  The  fractionation based  on  the  distilling  times, these  were first  fraction 0 7 hours,  second fraction  8 14  hours,  and  third fraction  15   24 hours.The results indicated that third fraction have met with Indonesia  Industrial  Standard  requirement, but specific gravity of  the  first and  second  fraction have not met the  requirement.  Acid   number   of  all fraction   have met  requirement  for ylangylang  oil.  Ester  number  of  the  third fraction  proximated  the ester of ylangylang  oil. Ester number  and ester content of  the  first  fraction   had a  higher  than  the  second  fraction and  this fraction had a higher  than  the  third fraction.  So, the first  fractional  distilled   cananga oil possesed  the  highest  quality. These  quality  could  be increased  by the fractional  steam distillation  in vacum pressure,  and  the distilling  used fresh  cananga flowers.